Rate and risk of anterior cruciate ligament injury among sportswomen in Slovenia - Vauhnik, R.; Morrissey, M. C.; Rutherford, O. M.; Turk, Z.; Pilih, I. A.; Pohar Perme, M. (Journal of Athletic Training, 2011)
Context: Anterior cruciate ligament (ACL)-injury rate is greater among female athletes than among male athletes.